Pengembangan Media Flipbook untuk Analisis Jenis Kalimat di Kelas 5 SD Negeri 12 Kota Langsa - Armayanti Armayanti; Najwa Syahada Gusna; Seni Ayu Ana Tasya; Wildan Sajali Harahap; Juliati Juliati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study was to illuminate how students understand various types of sentences, especially single sentences, compound sentences, and compound sentences, and to develop and implement flipbooks as a learning aid in grade V of SD Negeri 12 Kota Langsa. This study was conducted through a qualitative approach using observation, interviews, and documentation to collect data. The results showed that conventional learning methods and the lack of interactive media caused most students to still have difficulty in distinguishing the structure and use of sentence types. There is evidence that the use of visual and interactive flipbook media can improve students' understanding and encourage them to actively participate in the learning process. Flipbooks are able to create a more interesting and meaningful learning environment, despite technical constraints such as limited digital devices. This study found that flipbooks are an effective alternative for teaching Indonesian to elementary school students by improving their language skills.